Moderate Muslim in Indonesia: Views of Muslim Elite toward Religious and Socio-political Issues - Ridwan Ridwan; Djayadi Hanan; M. Syafii Anwar (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This article explores the views of Muslim elites regarding religious and socio-political issues as a means of explaining moderate Islam in Indonesia. Specifically, its aim is to shed light on this matter by mapping the ideological spectrum of Muslim elites’ perspectives on significant religious and political issues. A solid understanding of the socio-political context and the viewpoints of the elite is a crucial step towards comprehending the development of religious and political attitudes among the general population and the resulting impact on the social and political progress of the country. Based on fieldwork, this article argues that the majority of Muslim elites lean towards a moderate stance when it comes to perceiving ideological matters. Nevertheless, some still exhibit a tendency towards conservatism. It is important to note that this study is limited in its geographical scope. Consequently, further research should encompass various regions of Indonesia to provide a more comprehensive and holistic perspective.